Development of an efficient protocol for genomic DNA extraction from mango (Mangifera indica) - DILRUBA ASHRAFUN N. MAJUMDER; LUTFUL HASSAN; MOHAMMAD A. RAHIM; MOHAMMAD A. KABIR (Smujo International, 2011)
Abstract. Majumder DAN, Hassan L, Rahim MA, Kabir MA. 2011. Development of an efficient protocol for genomic DNA extraction from mango (Mangifera indica). Nusantara Bioscience 3: 105-111. A simple and efficient method for genomic DNA extraction from woody fruit crops containing high polysaccharide levels has been described here. In the present study, three kinds of plant DNA extraction protocols were studied and the target was to establish the water-saturated ether (WSE) with 1.25 M NaCl method as the most efficient protocol for removing the highly concentrated polysaccharides from genomic DNA of woody fruit crops. This method involves the modified CTAB or SDS procedure employing a purification step to remove polysaccharides using the WSE method. Precipitation with an equal volume of isopropanol caused a DNA pellet to form. After being washed with 70% ethyl alcohol, the pellet became easily dissolved in TE buffer. Using these three methods, DNA was extracted from samples of 60 mango genotypes, including young, mature, old, frosted old and withered old leaves. Compared with the three studied DNA extraction protocols of mango, it was found that the WSE method with NaCl had the highest value of average percentage (85.44%) in DNA content of the mango genotypes. The average yield of DNA ranged from 5.05 µg/µL to11.28 µg/µL. DNA was suitable for PCR and RAPD analyses and long-term storage for further use.